Development of Learning Tools based on the Discovery Learning Model Integrating 21st Century Skills in Trigonometric Materials in High Schools - Ade Putri; Kartini Kartini; Putri Yuanita (Universitas Riau, 2020)
This research is based on the limited discovery learning based learning tools that integrate 21st-century skills. The purpose of this study is to produce a valid and practical discovery learning-based of the learning tools that integrate to 21st-century skills in trigonometric material. The development model used the 4D model which consists of the define, design, develop, and disseminate stages. The tools being developed were syllabus, lesson plans, and student worksheets. The instrument used was a validity instrument in the form of a validation sheet, practical instruments in the form of student response questionnaires, and observation sheets. The data collection technique was carried out by distributing questionnaires and observations. The limited trials were conducted on 16 students of class XII MIPA 1 SMA Babussalam Pekanbaru, while practicality trials were carried out in class XI MIPA 2 SMA Babussalam Pekanbaru. The data analysis technique used in this research is quantitative data analysis and qualitative data analysis. From the results of data processing obtained an average syllabus validation result of 3.20; lesson plans 3.36; and student’s worksheet 3.43. The average student response questionnaire results in limited trials and field trials were 85.75% and 91.25%, respectively, with the very practical category. The average result of the observation sheet on the implementation of learning activities was 87%. It can be concluded that the learning tools developed are valid and practical.